Aplicação e adaptação da metodologia paver para pavimentos urbanos do Campus do Pici na cidade de Fortaleza - Sucupira, Marcos Lima Leandro (2006)
The necessity of constant maintenance and restoration services of the urban ways, aggravated by the lack of proper and sufficient resources, is the main motive for the application of management systems on urban pavements. These systems make it possible to allocate resources of the road infrastructure maintenance budget to the areas where they are most needed. By doing this, it becomes possible to optimize investments using them according to certain criteria, which will take into consideration the ways’ conservation status and also their importance. Within this context, this dissertation proposes an analysis of the existing distresses on urban pavements through the use of the PAVER methodology (Pavement Maintenance Management System), which was developed by the U.S. Army Corps of Engineers (USACE). Such methodologyis based on the Pavement Condition Index (PCI), which takes into consideration thetype of distress found and its severity level to calculate its value. In order to permit an analysis of ways with paving stone surfaces, which is frequently seen in Fortaleza, there have been some adaptations on the studied methodology by listing the existing distresses and evaluating their situation for the existing damages’ superficial area, once that this type of way is not approached by the PAVER methodology. In order to testthe efficiency of this way of analyzing urban pavements, a case-study has been conducted in a small portion, 604 meters long, of Fortaleza’s road network which is composed bytwo different paving surfaces; asphalt and paving stone. The results show the applicability of this methodology and the adaptation that has been developed, making it possible its implementation in big cities’ road networks in a Pavement Management System (PMS). Through the criteria of priorities, postulated by PAVER, one can provide a list of priorities of intervention in road network segments, the ones that really need intervention, as to reduce the waste of public resources and allow abetter spending control of these resources when restoration and maintenance services are being carried out in road networks.